Upaya Pencegahan Stroke Hemoragik dan Penilaian Activity Daily Living (ADL) pada Pasien Pasca Stroke - Yesi Astri; Trisnawati Mundijo; Isma Yulianti; Fadhilah Jasmine Shahab; Dhiya Ridha Shafira (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Stroke is one of the most common causes of mortality worldwide, and hypertension is a risk factor for stroke. The purpose of our activity is to increase the knowledge of stroke and hypertension in the community. This activity was conducted through counselling to 30 residents of RT 9, Kelurahan 14 Ulu, Seberang Ulu 2, Palembang, South Sumatera. Before and after counselling, a pretest and posttest were carried out to find out whether there was an effect of the counselling that had been given. In our conclusion, there are significant differences in knowledge about stroke and hypertension before and after counselling is given, with the average number of questions answered correctly by respondents from 5.06 to 6.30. Our study found that counselling activities and activity daily living assessments were able to increase knowledge and awareness of hypertension and stroke.